Морфологія сперматозоїдів та ендокринний статус чоловіків в умовах роботи з сільськогосподарськими добривами - Ломейко, Олена Олександрівна; Ломейко, Е. А.; Lomeiko, E. A. (Чорномор. нац. ун-т ім. Петра Могили, 2019)
У статті розглядаються особливості змін ендокринного статусу чоловіків та морфології сперматозоїдів в умовах роботи з сільськогосподарськими добривами. Встановлено, що особливістю змін ендокринного статусу в умовах контакту з сільськогосподарськими добривами є зниження рівня тестостерону (р<0,05), підвищення лютеїнізуючого (р<0,05) та фолікулостимулюючого гормонів (р<0,05). В умовах контакту з сільськогосподарськими добривами спостерігається зменшення загальної кількості сперматозоїдів (p<0,05), кількості сперматозоїдів на 1 мл еякуляту (p<0,05), сперматозоїдів з поступальним (p<0,05) та непоступальним (p<0,05) рухом. Зниження вмісту загального (p<0,05) та вільного тестостерону (p<0,05), загальної кількості сперматозоїдів (p<0,05), сперматозоїдів з поступальним рухом (p<0,05) залежить від тривалості професійного анамнезу. Діагностовано, що особливістю змін морфології сперматозоїдів в умовах контакту з сільськогосподарськими добривами є ураження всіх морфологічних параметрів спермограми - зменшення кількості нормальних за морфологією сперматозоїдів за строгим критерієм Крюгера (p<0,05), наявність аномальних сперматозоїдів та часта верифікація явища патозооспермії (p<0,05), діагностика фрагментації ДНК сперматозоїдів (p<0,05), патології акросоми та патології джгутика (p<0,05). Менш чутливим було виявлення патології голівок сперматозоїдів. Резюме. В статье рассматриваются изменения эндокринного статуса мужчин и морфологии сперматозоидов в условиях работы с сельскохозяйственными удобрениями. Установлено, что в условиях контакта с удобрениями снижается уровень тестостерона (р<0,05), повышаются лютеинизирующий (р<0,05) и фоликулостимулирующий (р<0,05) гормоны. В условиях контакта с сельскохозяйственными удобрениями наблюдается уменьшение общего количества сперматозоидов (p<0,05), количества сперматозоидов на 1 мл эякулята (p<0,05), сперматозоидов с поступательным (p<0,05) движением. Снижение содержания общего (p<0,05) и свободного тестостерона (p<0,05), общего количества сперматозоидов (p<0,05), числа сперматозоидов с поступательным и непоступательным движением (p<0,05) в условиях контакта с сельскохозяйственными удобрениями зависит от продолжительности профессионального анамнеза. Диагностировано, что особенностью изменений морфологии сперматозоидов является изменение морфологических параметров спермограммы - уменьшение количества нормальных по морфологии сперматозоидов по строгому критерию Крюгера (p<0,05), наличие аномальных сперматозоидов и частая верификация патозооспермии (p<0,05), диагностика фрагментации ДНК сперматозоидов (p<0,05), патологии акросомы и патологии жгутика (p<0,05). Менее чувствительным было выявление патологии головок сперматозоидов. Abstract. As numerous studies indicated, pesticides can be the important cause of male infertility. However, there is no characteristics of endocrine status, changes in spermogram parameters in men who contact with agricultural fertilizers and pesticides in our country. The purpose of the study was to research male infertility, peculiarities of endocrine status and morphology of spermatozoa in conditions of contacting with pesticides. Material and methods. We examined 48 men, whose occupational activity was related to contact with pesticides. The study of hormonal status, parameters of spermogramm was conducted in all patients. We used clinical examination, laboratory, microscopic and immunological research, analysis of parameters of spermogram and sonography. Hormonal panel (follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), progesterone, estradiol, testosterone) was held on analyzer "Rayto, 2000" with "Siemens" diagnostic kits. To determine the concentration and mobility of the sperm it was used microscope Biomed-4. The main parameters of the ejaculate were evaluated in accordance with guidelines of WHO's 5th edition, 2010. Results and discussion. It was established that changes in the endocrine status characterized with a probable decrease in the levels of total (p<0.05) and free testosterone (p<0.05), increase in luteinizing (p<0.05) and follicle-stimulating hormone (p<0.05) in comparison with the control group. We noted that in conditions of contact with agricultural fertilizers, there took place the probable reduction in the total spermatozoa number (p<0.05), the number of spermatozoa on 1 ml of ejaculate (p<0.05), the number of active spermatozoa (p<0.05). The decrease of total (p<0.05) and free testosterone (p<0.05), total sperm count (p<0.05) and number of active spermatozoa (p<0.05) depended on the duration of professional history and was characterized by a progressive decrease with a longer working experience. Having performed the analysis of diagnostic sensitivity we diagnosed that morphological features in the conditions of contact with agricultural fertilizers was the defeat of all morphological parameters of spermogram. It was the decrease of normal sperm number according to Kruger criterion (p<0.05), the presence of abnormal sperm and pathosospermia (p<0.05), DNA fragmentation (p<0.05), acrosomal pathology and flagella pathology (p<0.05). The detection of sperm head pathology was less sensitive. Conclusion. The decreases of testosterone level, changes of morphological parameters in spermogram are common syndromes of male infertility in conditions of contacting with pesticides.
Морфология сперматозоидов и особености эндокринного статуса мужчин в условиях работы с сельскохозяйственными удобрениями
Morphology of spermatozoids and features of male endocrine status in men working with agricultural fertilizers
Keywords: ендокринний статус; сперматозоїди; морфологічні зміни; чоловіча інфертильність; сільськогосподарські добрива; эндокринный статус; сперматозоиды; морфологические изменения; мужская инфертильность; сельскохозяйственные удобрения; endocrine status; spermatozoa; morphological changes; male infertility; agricultural fertilizers